Diseño y construcción de un sistema inteligente de control de bombas de agua en cultivo de fresas (Fragaria) - Huayanay Villar, José Luis (2024)
The objective of the work is to develop an intelligent irrigation system around microcontrollers (for example, Arduino, Funduino, etc.) for strawberry (Fragaria) crops. The system is an improvement of the first versions "Design and construction of an automated control system for water pumps in a hydroponic crop in the Arduino environment, UNSCH - Ayacucho" and "Sliding mode controllers for soil moisture modeled by Differential equation nonlinear parabolic partial” published in 2020 and 2021 respectively by the same author, the relay modules in this version have several channels, electrical resistances and adaptable to photovoltaic energies; In order to obtain a programmable microcontroller system that can activate and deactivate the water pump of a greenhouse at certain times according to the development of the crop, particularly in strawberry crops, for this it is necessary to use different control techniques and perform various experimental tests in order to adjust certain control parameters, especially humidity and temperature. This system was installed in the greenhouse of the company VILLA AUTOMATION EIRL in Huanta-Ayacucho, within the annual research agreement between the National University of San Cristóbal de Huamanga (UNSCH) and the Peruvian manufacturing company VILLA AUTOMATION EIRL-RUC 20610009400.